MENGANALISIS PERKEMBANGAN HASIL BELAJAR BIOLOGI PESERTA DIDIK PADA METODE RESITASI DI SMA NEGERI 1 LUAHAGUNDRE MANIAMOLO - Silvia Sri Intan Wau (TUNAS : Jurnal Pendidikan Biologi, 2024)
The objectives of this research are as follows: 1) to determine the results of biology learning given to students of SMA Negeri 1 Luahagundre Maniamolo using the recitation method; and 2) to find out the factors that influence biology learning outcomes. This type of research is qualitative research. The subjects in this research were biology teachers and 23 students in class XI MIA of SMA Negeri 1 Luahagundre Maniamolo in 2023. The results of the research show that students can develop the ability to understand biology learning and can be accountable for what they have done. So it can be concluded that students at SMA Negeri 1 Luahagundre Maniamolo experienced good changes in the biology learning process with interactions between teachers and students and students with other students, including the development of autonomous attitudes, awareness, will and self-motivation. The suggestions put forward by researchers are 1) Researchers should be able to find out students' learning outcomes in developing their own processing skills in understanding material by using the recitation method in the learning process. 2) Teachers should prepare learning methods first before carrying out the learning process in the classroom, so that they can find out students' learning outcomes. And 3) Students should be more active in class by understanding biology material independently in the learning process.